Between aspect and negation: The heterosemy of [deixar+de+vinf.] - Júnior, José Roberto Prezotto [UNESP]; Gonçalves, Sebastião Carlos Leite [UNESP] (University of Minho, 2021)
Founded on the theoretical and methodological premises of the Usage-Based Models (Bybee 2016; Goldberg 1995, 2006; Traugott & Trousdale 2013), in this paper, we analyze the micro-construction [deixar+de+Vinf.] from the semantic domains of aspect and polarity. Since they are linked, by a heterosemy link (Lichetenberk 1991), in different taxonomic networks of Portuguese, we demonstrate that these micro-constructions originate from the transitive construction with the verb deixar, whose central meaning is distancing. Based on data extracted from the Corpus do Português (Davis & Ferreira 2006, 2016), we describe the singularities of the micro-constructions through a diachronic quantitative and qualitative analysis of parameters semantic entity type represented by the subject of the micro-construction and semantic type of Vinf.,. At the end, the results allow us to prove the hypothesis that these micro-constructions emerge from relations with other ones already existing and they gradually abstract sanctioning a greater variety of semantic subject and Vinf. types.
Entre aspecto e negação: A heterossemia de [deixar+de+vinf.]
Keywords: Aspectuality; Heterosemy; Periphrasis; Polarity